2008
DOI: 10.3325/cmj.2008.49.763
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Abstinence and Well-being of Alcohol-dependent Patients after Intensive Treatment and Aftercare Telephone Contacts

Abstract: Significant differences in well-being variables between telephone contact group and no contact group at 24 months after the end of intensive treatment are at least partially due to phone contact/informative checking 3, 6, and 12 months after the end of intensive therapy. Telephone or any short and easy accessible communication checking is a promising as supportive and research tool in aftercare alcohol addiction treatment, especially because of its cost-benefit advantages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
1
8
1
1
Order By: Relevance
“…Our results are also consistent with Rus-Makovec and Cebasek-Travnik (2008) who found that adult alcohol-dependent patients who received four telephone contacts in two years were significantly higher on subjective well being than those who did not, although abstinence rates were not different.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are also consistent with Rus-Makovec and Cebasek-Travnik (2008) who found that adult alcohol-dependent patients who received four telephone contacts in two years were significantly higher on subjective well being than those who did not, although abstinence rates were not different.…”
Section: Discussionsupporting
confidence: 92%
“…A total of eight studies reported on the course of employmentrelated difficulties. Five of these studies reported improvement [68], while two studies reported improvement/stability [69,29], The most frequent determinants for positive evolution were treatment interventions (reported by five different studies), including two pharmacotherapies [68,70], and improvement in drinking status (reported by three studies). Treatment in general was considered a positive determinant in three studies [20].…”
Section: R Em Unerative Em P Lo Ym E N T (D850)mentioning
confidence: 95%
“…Problems in intimate relationships referred to problems in spousal or comparable relationships and were reported 34 times in 31 studies. One study including only females identified the onset of spousal problems: namely, traumatic and deprived childhood environments [57], The evolution of spousal problems was identified six times in six studies, five reporting improve ments [58] and one improvement or no change [29], Four studies reported on the determinants of improvement; in three of these, treatment interventions were central [59]. No treatment regime was reported more frequently than another to instigate positive change.…”
Section: Icf Category Icf Subcategorymentioning
confidence: 97%
See 1 more Smart Citation
“…Telephone delivery is one non face-to-face method, and literature has found telephone-administered interventions to be feasible (Carter et al 2008; Hubbard et al 2007; Mbilinyi et al 2011; McKay et al 2011) and effective in individuals with a substance use disorder in primary care (Bischof et al 2008; Brown et al 2007; Oslin et al 2003; Stotts, Diclemente & Dolan-Mullen 2002; Tait et al 2007; Zanjani, Bush & Oslin 2010; Zanjani et al 2008) and addiction-focused settings (Cacciola et al 2008; Chong & Herman-Stahl 2003; Godley et al 2010; Hall & Huber 2000; Horng & Chueh 2004; Karno et al 2012; McKay et al 2010; Mulleady 2001; Parker, Turk & Busby 2002; Rus-Makovec & Cebasek-Travnik 2008). Telephone delivery is commonly believed to overcome treatment barriers present in traditional face-to-face delivery.…”
Section: Introductionmentioning
confidence: 99%